2013
DOI: 10.1371/journal.pone.0057147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plasma Membrane Cholesterol Level and Cytoskeleton F-Actin on Cell Protrusion Mechanics

Abstract: Protrusions are deformations that form at the surface of living cells during biological activities such as cell migration. Using combined optical tweezers and fluorescent microscopy, we quantified the mechanical properties of protrusions in adherent human embryonic kidney cells in response to application of an external force at the cell surface. The mechanical properties of protrusions were analyzed by obtaining the associated force-length plots during protrusion formation, and force relaxation at constant len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 49 publications
(57 reference statements)
4
45
0
Order By: Relevance
“…These results indicated that interaction of the actin cortical cytoskeleton was stronger with membranes containing lower amount of cholesterol. A follow up work from the same group, now also using cells treated with latrunculin, confirmed previous results showing that cholesterol disruption alters membrane interaction with the actin cytoskeleton leading to increased cell stiffness [57]. These results also confirmed that both plasma membrane and cytoskeleton contribute to the viscoelastic behavior observed for the membrane tethers.…”
Section: De Oliveira Andrade / the Power Of Imagingsupporting
confidence: 84%
See 1 more Smart Citation
“…These results indicated that interaction of the actin cortical cytoskeleton was stronger with membranes containing lower amount of cholesterol. A follow up work from the same group, now also using cells treated with latrunculin, confirmed previous results showing that cholesterol disruption alters membrane interaction with the actin cytoskeleton leading to increased cell stiffness [57]. These results also confirmed that both plasma membrane and cytoskeleton contribute to the viscoelastic behavior observed for the membrane tethers.…”
Section: De Oliveira Andrade / the Power Of Imagingsupporting
confidence: 84%
“…Additionally and most important, they showed that the effects of plasma membrane itself in mechanical properties of cells are relatively minor in comparison with the effects of the cytoskeleton. On the other hand, changes in plasma membrane content, as in the case of cholesterol, might induce changes in the cytoskeleton and therefore indirectly contribute to cellular mechanical properties [57]. These results were corroborated by a work from our group, showing that the levels of the plasma membrane cholesterol content influence cell rigidity [51].…”
Section: De Oliveira Andrade / the Power Of Imagingsupporting
confidence: 73%
“…Cholesterol: methyl-β-cyclodextrin complex (Sigma catalog no. C4951), a "water-soluble cholesterol" containing 47 mg of cholesterol/g solid according to Certificate of Analysis (molar ratio, 1:6 cholesterol/ methyl-β-cyclodextrin) was used to deliver cholesterol to the cells, as previously described [9,32,33]. Considering that methyl-β-cyclodextrin induces mitochondrial cholesterol depletion from cell membranes at very high concentration ($ 2% or 5 mM) [32,34], a ten times lower concentration of this compound in our experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the raft-disrupting agent, MβCD, plays a negative regulation role in the 2D receptor-ligand interactions from this perspective. However, more studies reveal that the effect of cholesterol depletion on the membrane bending rigidity is not universal but rather depends on the cell type and lipid architecture [59][60][61][62]. Therefore, the potential contributions of MβCD to the receptor-ligand interactions may be specific to the type of cells and lipids.…”
Section: Fig 8 (A)mentioning
confidence: 99%